EFEKTIVIFITAS DAN EFISIENSI PEMBELAJARAN DARING DI SEKOLAH MENENGAH PERTAMA - Andi Fatmayanti (Lembaga Penelitian Dan Pengabdian Masyarakat Institut Agama Islam Sultan Muhammad Syafiuddin Sambas Kalimantan Barat, 2022)
This study aims to examine the level of effectiveness and efficiency of online learning in schools with a total sample of 91 students. This research is quantitative in nature using a descriptive survey research method that aims to collect data and describe an existing symptom, namely the effectiveness and efficiency of online learning during Covid-19. The data collection technique used is a questionnaire, by applying self-administered questionnaires. The questionnaire uses a closed statement with a Likert scale measurement procedure with data analysis techniques consisting of the editing stage, data input stage, and tabulation stage. At this stage the data that has been inputted is then calculated the frequency and percentage. The results of the study showed that the online method during the pandemic had an effect of 41.8% on the effectiveness of learning and 38, 44% on learning efficiency. It is concluded that the effectiveness and efficiency of online learning is still in the poor category caused by two main things, namely the uneven development of technology, and the low pedagogic competence of teachers, so it is necessary to evenly distribute the development of technology quality and improve the quality of teacher competence.